2003
DOI: 10.2307/30040665
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Human Resource Practices, Top Management Team Social Networks, and Firm Performance: The Role of Human Resource Practices in Creating Organizational Competitive Advantage.

Abstract: In this article, we begin to explore the black box between human resources (HR) practices and firm performance. Specifically, we examine the relationships between a set of network-building HR practices, aspects of the external and internal social networks of top management teams, and firm performance. Results from a field study with 73 high-technology firms showed that the relationships between the HR practices and firm performance (sales growth and stock growth) were mediated through their top managers' socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
598
0
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 997 publications
(643 citation statements)
references
References 37 publications
17
598
0
28
Order By: Relevance
“…Guest (1997) shows that strategic HRM (SHRM) improves firm performance by enhancing employees' skills and abilities. Collins and Clark (2003) provide support for the mediating role of social structure. They examine the mediating effect of social networks of top management teams (TMTs) on the relationship between HRM and firm performance.…”
Section: Literature Review and Propositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guest (1997) shows that strategic HRM (SHRM) improves firm performance by enhancing employees' skills and abilities. Collins and Clark (2003) provide support for the mediating role of social structure. They examine the mediating effect of social networks of top management teams (TMTs) on the relationship between HRM and firm performance.…”
Section: Literature Review and Propositionsmentioning
confidence: 99%
“…More specifically, Youndt et al (1996) demonstrate that a human capital-enhancing HR system has a direct positive relationship with multiple dimensions of a firm's operational performance, such as employee productivity, machine efficiency, and customer alignment. Collins and Clark (2003) indicate that network-building HR practices positively relate to organizational performance, that is, growth in sales and stock return. Huselid (1995) illustrates a positive relationship between high performance work practices and organizational turnover, productivity, and financial performance.…”
Section: Literature Review and Propositionsmentioning
confidence: 99%
“…Although previous studies discovered that sophisticated HR planning, recruitment and selection, and training are associated with both high labor productivity and organizational performance [6] [30], the relationship is not as strong as expected [2] [5] [9] [18] in particular, found no significant impact of technical HRM on firm performance. The indication of these findings is that technical HRM alone may not have good predictive power to explain organizational performance.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 82%
“…For instance, Bhattacharya et al, [18] reported that employees' skills, behaviors, and HRM flexibility together explain 8% of incremental variance in the financial performance of an organization. Collins et al, [9] found that network-building HR activities explained about 7% of sales growth. These findings call for further studies from different perspectives, such as investigating HRM as a system rather than as a result of an individual HR activity, examining both technical HRM and strategic HRM, and exploring different performance criteria [5] [6] [19].…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Es fundamental, por tanto, que la organización asuma la importancia de saber identificar y valorar adecuadamente esos procesos clave en el ámbito de la gestión de personas, entre los que destacan la identificación y desarrollo de las habilidades directivas, entre las que la inteligencia emocional ocupa un papel muy destacado. En este sentido, las prácticas de recursos humanos son el principal medio por el que las organizaciones, públicas o privadas, pueden influir en las habilidades, actitudes y comportamientos de los trabajadores y, a través de ello, en los resultados organizativos (Collins y Clark, 2003).…”
Section: El Artículo Presenta Una Investigación Sobre La Inteligenciaunclassified